Evaluation of the effects of radiocontrast agents on the inner ear with audiological and histopathological parameters - Dogan R.; Kucuk R. B.; Basoz M.; Ozturan O.; Yenigun A. (My University, 2026)
Background Radiocontrast agents are widely used in diagnostic and interventional imaging. While their nephrotoxic effects have been well documented, data regarding their potential ototoxicity remain limited. Notably, cochlear cells share structural similarities with renal tubular cells, suggesting a potential susceptibility to contrast-induced damage. Only one experimental study and a few case reports have investigated the auditory effects of these agents. This study aimed to evaluate the effects of radiocontrast agents with different osmolarities; high (HOCM), low (LOCM), and iso-osmolar (IOCM) on the inner ear using audiological and histopathological methods. Results Thirty-two Sprague Dawley rats were randomly assigned to four groups receiving HOCM, LOCM, IOCM, or saline (control) intravenously. Distortion product otoacoustic emissions (DPOAE) and auditory brainstem response (ABR) tests were conducted at baseline, day 7, and day 14. Histopathological evaluations were performed on cochlear tissues after the final assessments. No significant differences were observed in DPOAE amplitudes or ABR thresholds between groups or across time points (p > 0.05). Histologically, cochlear architecture, including hair cells, spiral ganglion cells, and nerve fibers, remained intact in all groups, with no evidence of degeneration or cellular loss. Conclusions This study found no audiological or histopathological evidence of ototoxicity following administration of HOCM, LOCM, or IOCM at standard doses. These findings suggest that radiocontrast agents, regardless of osmolarity, do not impair cochlear function under typical clinical conditions. The inclusion of IOCM, which has the closest osmolarity to plasma, further supports its safe profile. While our results are reassuring, further studies are warranted to assess the effects of higher doses, repeated exposures, and comorbid conditions such as renal impairment.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp; Klinik Tıp (Med); Otorhinolaryngology; Clinical Medicine; Clinical Medicine (Med); Konuşma ve İşitme; Speech and Hearing